Towards a Reliable and Sustainable Source of Electricity for Micro and Small Scale Light Industries in the Kumasi Metropolis - Owusu, Amponsah (2011)
A Thesis Submitted to the Department of Planning, Kwame Nkrumah University of Science and Technology Kumasi,In Partial fulfilment of the requirements for the Degree of Master of Science in Development Policy and Planning, 2010